Low flow analysis for Kuantan river basin - Nur Ain Izani, A Rahim (2018)
Low flow analysis study is done to provide decision makers with surface-water information needed for activities such as water-quality regulation, biological habitat assessment, infrastructure design, and water-supply planning and management. The flow statistics, which included annual period of record flow durations and average minimum flow 7-day were computed at one streamflow-gaging stations which located at Bukit Kenau. For streamflow-ungauging station, 17 catchment in Kuantan River Basin were selected to analyse low flows, including the 1, 4, 7 and 30 consecutive-day low flows with recurrence intervals of 1.5, 2.33, 5, 10, 20 and 50 years. Daily mean streamflow data were taken from Department of Irrigation and Drainage (DID) from year 1975 until 2014. The main objective of this study is to estimate the low flow and analyse the low flow trend from year 1975 until 2014. In addition, low flow data helps to indicate the probable availability of water in streams when conflict arise between water supply and demand. Streamflow gauging station is rank by using Weibull’s equation while for ungauging station, the regression equation in Hydrological Procedure No. 12 were used to estimate the low flow. Regional frequency analysis were developed for estimating low flow values at streamflow ungauged station. From gauging station analysis, the highest minimum flow is 36.5 m3/s in year 2012 while the lowest minimum flow is 0.1 m3/s in year 2013. Meanwhile from ungauging station, area of the basin give impact to the discharge as the larger the area, the higher the discharge. Chereh with an area of 227.51 km2has the highest discharge in 50 years with 0.87 m3/s while Sg. Isap with the smallest area with only 4 km2has the lowest discharge which is 0.00216 m3/s.